Association Between Preoperative Hydronephrosis and Prognosis After Radical Cystectomy Among Patients With Bladder Cancer: A Systemic Review and Meta-Analysis - Oh, Jong Jin; Byun, Seok-Soo; Jeong, Chang Wook; Kwak, Cheol; Kim, Hyeon Hoe; Ku, Ja Hyeon (Frontiers in Oncology, 2019)
Background: Preoperative hydronephrosis (HN) might be associated with adverse outcomes in patients who underwent radical cystectomy (RC). The aim of this study was to evaluate the effect of preoperative HN on the oncological outcomes in patients with bladder cancer who underwent RC by performing a systemic review and meta-analysis. Methods: A systematic literature review in PubMed, EMBASE, and Scopus was conducted by searching the terms “bladder cancer,” “cystectomy,” and “hydronephrosis” until December 2016, in accordance with the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) guidelines. The calculated end points were advanced disease stage, cancer-specific survival (CSS), and overall survival (OS). Results: Twenty-four studies involving 10,461 patients who underwent RC were included. Among the patients, 3,121 (29.8%) had preoperative HN. The pooled analysis showed that preoperative HN had a significant association with advanced stage (odds ratio, 2.56, 95% confidence interval [CI], 1.91–3.42, p < 0.00001), lymph node invasion (OR, 2.44, 95% CI, 1.79–3.34, p < 0.00001), CSS (hazard ratio [HR], 1.67, 95% CI, 1.34–2.08, p < 0.00001), and OS (HR, 1.51, 95% CI, 1.30–1.75, p < 0.00001). Conclusions: Among patients with bladder cancer who underwent RC, preoperative HN could be a significant predictor of bladder cancer survival. However, large well-designed prospective studies are required to confirm the precise prognostic significance of preoperative HN.